Mathefreaker2021

avatar
Nom d'utilisateurMathefreaker2021
But939
Membership
Stats
Questions 73
Réponses 261

 #1
avatar+939 
0

(a) The left-hand side counts the number of ways to choose k elements from a set of n - 1 elements. The first term, C(n - 1, k - 1), counts the number of ways to choose k - 1 elements, and the second term, C(n - 1, k), counts the number of ways to choose k elements. To form the set of k elements in C(n, k), we simply add an element n to each of these two sets. So, C(n - 1, k - 1) + C(n - 1, k) = C(n, k).

(b) The left-hand side counts the number of ways to choose 0 to n elements from a set of n elements. For each positive integer i from 0 to n, C(n, i) counts the number of ways to choose i elements. The sum on the left-hand side is equivalent to counting the number of possible combinations of n elements, which is 2^n.

(c) The left-hand side counts the number of ways to choose 0 to k elements from a set of n + k elements. Each term C(n + i, i) counts the number of ways to choose i elements from a set of n + i elements. The sum on the left-hand side is equivalent to counting the number of possible combinations of n + k elements, which is C(n + k + 1, k).

(d) The left-hand side counts the number of ordered pairs (X, Y) where X is a set of r elements selected from a set of m elements and Y is a set of r elements selected from a set of n elements. For each positive integer i from 0 to r, C(m, i) C(n, r - i) counts the number of ordered pairs where X has i elements and Y has r - i elements. The sum on the left-hand side is equivalent to counting the number of possible combinations of r elements from the set of m + n elements, which is C(m + n, r).

(e) The left-hand side counts the number of ordered pairs (a, b) of positive integers where 1 <= a, b <= n. The expression (n + 1)^2 - 2n - 1 counts the total number of ordered pairs of positive integers where 1 <= a, b <= n + 1 and then subtracts the ordered pairs (n + 1, n + 1) and (n + 1, i) for 1 <= i <= n, as well as (i, n + 1) for 1 <= i <= n. This gives us the total number of ordered pairs of positive integers where 1 <= a, b <= n.

(f) The left-hand side counts the number of ordered triples (a, b, c) of positive integers where 1 <= a, b, c <= n. The expression (n + 1)^3 - 3n^2 - 3n - 1 counts the total number of ordered triples of positive integers where 1 <= a, b, c <= n + 1 and then subtracts the ordered triples (n + 1, n + 1, n + 1), (n + 1, n + 1, i), (n + 1, i, n + 1), and (i, n + 1, n + 1) for 1 <= i <= n, as well as all ordered triples where at least one element is equal to n + 1. This gives us the total number of ordered triples of positive integers where 1 <= a, b, c <= n.

11 févr. 2023
 #1
avatar+939 
0

This inequality can be proven using the Cauchy-Schwarz inequality.

Let \(x = sqrt(a^2 + ab + b^2), y = sqrt(a^2 + ac + c^2)\), and \(z = sqrt(b^2 + bc + c^2)\), then we can rewrite the inequality as:

\(x + y + z >= sqrt(3) (sqrt(ab) + sqrt(ac) + sqrt(bc))\)

Squaring both sides, we get:

\((x + y + z)^2 >= 3 (sqrt(ab) + sqrt(ac) + sqrt(bc))^2\)

Expanding the left-hand side, we get:

\(x^2 + y^2 + z^2 + 2xy + 2xz + 2yz >= 3 (sqrt(ab) + sqrt(ac) + sqrt(bc))^2\)

Expanding the right-hand side, we get:

\(x^2 + y^2 + z^2 + 2xy + 2xz + 2yz >= 3 (ab + ac + bc + 2 sqrt(ab) sqrt(ac) + 2 sqrt(ab) sqrt(bc) + 2 sqrt(ac) sqrt(bc))\)

Using the Cauchy-Schwarz inequality, we have:

\(2xy + 2xz + 2yz >= 2 (sqrt(ab) sqrt(ac) + sqrt(ab) sqrt(bc) + sqrt(ac) sqrt(bc))\)

Substituting this into the previous inequality, we get:

\(x^2 + y^2 + z^2 + 2xy + 2xz + 2yz >= 3 (ab + ac + bc) + 2 (sqrt(ab) sqrt(ac) + sqrt(ab) sqrt(bc) + sqrt(ac) sqrt(bc))\)

Using the definition of x, y, and z, we get:

\((a^2 + ab + b^2) + (a^2 + ac + c^2) + (b^2 + bc + c^2) + 2 sqrt((a^2 + ab + b^2)(a^2 + ac + c^2)) + 2 sqrt((a^2 + ab + b^2)(b^2 + bc + c^2)) + 2 sqrt((a^2 + ac + c^2)(b^2 + bc + c^2)) >= 3 (ab + ac + bc) + 2 (sqrt(ab) sqrt(ac) + sqrt(ab) sqrt(bc) + sqrt(ac) sqrt(bc))\)

Combining like terms and rearranging, we get:

\(2 (sqrt((a^2 + ab + b^2)(a^2 + ac + c^2)) + sqrt((a^2 + ab + b^2)(b^2 + bc + c^2)) + sqrt((a^2 + ac + c^2)(b^2 + bc + c^2))) >= 2 (sqrt(ab) sqrt(ac) + sqrt(ab) sqrt(bc) + sqrt(ac) sqrt(bc))\)

So, the inequality is proven.

Equality occurs when x = y = z, which means\( a^2 + ab + b^2 = a^2 + ac + c^2 =\)

.
11 févr. 2023